1991
DOI: 10.1111/j.1471-0528.1991.tb15335.x
|View full text |Cite
|
Sign up to set email alerts
|

(Patho)physiological implications of chronic dietary sodium restriction during pregnancy; a longitudinal prospective randomized study

Abstract: Objective-To study the possible pathophysiological implications of long continucd dietary sodium restriction in pregnancy. Design-Longitudinal prospcctive randomized study of the effects of a low sodium diet compared with unrestricted sodium intakc in prcgnancy. of Rcproduction T. K. A . B. ESKES Professor P. R. HEIN Senior Lc,ctrirer in Obstetrics promptcd by thc belief that excessive retention of sodium and water is the main cause of prceclampsia and eclampsia in particular (Cramer 1906; Dc Snoo 1Y37).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…An identical AVP (and All) receptor type (Via) is expressed on the vascular smooth muscle cell and platelet and earlier we described a (not significant) decrease in platelet AVP maximal binding capacity during third trimester pregnancy (van der Post et ai 1993), compared with outside pregnancy. During sodium restric tion in human pregnancy, an increase in vascular periph eral resistance is found (Steegers et al 1991). The unaltered AVP platelet binding found by us does not indicate a role for the VI a-A VP receptor type in the increased vascular resistance found during sodium restriction.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…An identical AVP (and All) receptor type (Via) is expressed on the vascular smooth muscle cell and platelet and earlier we described a (not significant) decrease in platelet AVP maximal binding capacity during third trimester pregnancy (van der Post et ai 1993), compared with outside pregnancy. During sodium restric tion in human pregnancy, an increase in vascular periph eral resistance is found (Steegers et al 1991). The unaltered AVP platelet binding found by us does not indicate a role for the VI a-A VP receptor type in the increased vascular resistance found during sodium restriction.…”
Section: Discussionmentioning
confidence: 48%
“…This again indi cates unaltered circulating levels of AVP since free plasma AVP and platelet-bound AVP are positively correlated (see Results). O n the other hand, the reduction in plasma volume (Brown 1988) or cardiac output during sodium restriction (Steegers et al 1991) might normalize a dietaryinduced decrease in platelet-bound AVP, since nonosmotic stimuli like reduced cardiac output increase platelet-bound AVP in non-pregnant subjects (Preibisz et al 1983). It indicates that reduction in effective circu lating volume during sodium restriction in pregnancy (Steegers et a i 1991) does not lead to non-osmotic AVP release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a former prospective randomised study in healthy nulliparous women we found no significant influence on blood pressure of chronic dietary sodium restriction started in the early second trimester. 28 Knuist and co-workers recently published the results of a trial of sodium restriction in late pregnancy in nulliparous women. 29 Two hundred and thirty-three women who were normotensive in the first half of pregnancy were randomised to either a low sodium or an ad libitum diet after diastolic blood pressure had risen to or above a threshold value of 85 mm Hg in the second half.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of dietary salt restriction in pregnancy have shown no major changes in blood pressure. 6,7 However, there is a decrease in extracellular fluid volume, a reduction in the amount of weight gain across pregnancy, and a lower stroke volume and cardiac output. The systemic vascular resistance is significantly higher than in pregnant women with unrestricted diets.…”
Section: Churchillmentioning
confidence: 99%